Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai pada Badan Pengelola Pajak dan Restribusi Daerah Muaro Jambi - Endang Dofitria Angraini (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This reseach was  to analyse how the effect of motivation and dicipline on job performance . How to as well as a condition of motivation, dicipline and job performance at the Tax Management and Restrition of Muaro  Jambi Area.The research methodology is descriptive and quantitative analysis methods. Data used is secondary data.The population become object in this research is job performance at Tax Management and Restrition of Muaro  Jambi Area. The method for analysis is analysis multifly regression, hypotesis test, correlation so determinant coefficient and F_tes so t_test. The object of this research is the Tax Management and Restrition of Muaro  Jambi Area. This office is a branch of Tax Management and Restrition of Muaro  Jambi Area, which is the task of collect tax on earth and buildings and other taxes in the Muaro Jambi area.Analysis on the research of respondents felt a high motivation and work discipline in the performance of tasks provided by the superiors. In the statement of respondents the indicator comes and home work on time shows the hihest score, which is a score of 280 verry high categories. Multiple linear regression equations are Y = 8,266 + 0.243X1 + 0.740X2 + E. Independent variables (motivation and work discipline) simultaneously have significant effect on the dependent variables (performance of members). While partial motivation affects performance and variable work discipline affects of the performance. Conclusion that the motivation and discipline have significant effect on performance and have a positive relationship in Tax Management and Restrition of Muaro  Jambi Area.